Constraints Analysis of Joint Forest Management Programme in Jammu Division of Jammu and Kashmir - Iqbal, Tariq; Slathia, P.S.; Peshin, Rajinder; Sehgal, Sandeep; Sharma, Manish Kumar; Kour, Kiran; Kumar, Rakesh (Indian Journal of Extension Education, 2021)
The study was conducted in purposively selected “East Forest Circle” of Jammu division of J&K. Multistage sampling was followed for the selection of respondents from six forest ranges from East circle, having maximum number of Joint Forest Management Committees (JFMCs) purposively. Twenty four committees, four from each selected ranges of and eight members from each selected JFMC were selected through random sampling technique making the sample size of 192 respondents. Total 192 JFMC members were interviewed to find out the constraints faced in Joint Forest Management Programme. Henry Garrett’s ranking technique was used to analyse the constraints. The result showed that respondents ranked Lack of funds, Delay in planting time, lack of training programme as major constraints in respective order.
Keywords: Joint forest management; Constraints; Ranges; Forest; Ranking